Laparoscopic Management of Incarcerated Femoral Hernia with Bowel Necrosis: A Case Report - Handito Sarwwotatwadhiko; Anung Noto Nugroho (Open Access Indonesian Journal of Medical Reviews, 2025)
Femoral hernias, though representing less than 5% of all abdominal wall hernias, pose a significant clinical challenge due to their anatomical constraints and high complication rates. Exhibiting a pronounced female predominance, these hernias carry a substantial risk of incarceration and strangulation, estimated between 5-20%, stemming from the narrow and unyielding nature of the femoral canal. This anatomical predisposition frequently mandates urgent surgical intervention to prevent bowel ischemia and necrosis. Diagnostic difficulties often arise, particularly in occult presentations lacking a discernible groin mass. The advent of laparoscopy has revolutionized the approach, offering distinct advantages in both the diagnosis of clinically obscure hernias and the execution of minimally invasive repair, potentially improving patient outcomes. We present the case of a 63-year-old female who arrived at the emergency department complaining of a three-day duration of severe, intermittent abdominal pain associated with obstipation, progressive abdominal distension, nausea, and vomiting. Clinical examination revealed marked abdominal distension but failed to identify any palpable mass in the inguinal or femoral regions. Plain abdominal radiography indicated findings consistent with small bowel obstruction. Consequently, an exploratory laparoscopy was undertaken. Intraoperatively, an incarcerated right femoral hernia was discovered, containing a 4 cm segment of ileum that exhibited frank necrosis. A completely laparoscopic procedure involving small bowel resection, creation of a side-to-side ileoileal anastomosis, and subsequent repair of the femoral hernia defect using primary purse-string sutures was performed successfully. In conclusion, the laparoscopic approach was indispensable for the accurate diagnosis and effective management of this complex case involving an occult, incarcerated femoral hernia with resultant bowel necrosis. Employing a minimally invasive strategy facilitated simultaneous bowel resection and hernia repair, offering potential benefits including diminished postoperative discomfort, expedited recovery, and possibly lower long-term recurrence rates relative to traditional open surgical techniques. This case reinforces the critical importance of considering femoral hernia in the differential diagnosis of female patients presenting with acute small bowel obstruction, even in the absence of classical external signs. Furthermore, it underscores the feasibility and efficacy of a purely laparoscopic approach for managing such complex surgical emergencies.